Spinal dural arteriovenous fistula presenting with subarachnoid hemorrhage: A case report. Issue 16 (April 2018) - Han, Jingzhe; Cao, Duanhua; Wang, Hongmei; Ji, Ye; Kang, Zhilei; Zhu, Jianguo
Abstract: Rationale: Subarachnoid hemorrhage (SAH) is a common and serious disease and one of the most important differential diagnoses in the emergency department. Patient concerns: A 39-year-old female patient with a 12 years' history of migraine, presented with a sudden headache combined with motor aphasia. Physical examination suggested probable positive neck resistance. SAH was confirmed by magnetic resonance imaging. In addition, spinal digital subtraction angiography and spinal vascular computed tomography angiography indicated spinal arteriovenous malformation (SAVM). Diagnoses: The final diagnosis was spinal dural arteriovenous fistula presenting with SAH. Interventions: Following diagnosis, appropriate drugs were administered, but the therapeutic effect was poor. Then the patient was then transferred to a superior hospital where she was treated with interventional embolization. Outcomes: Through 2 years of follow-up, intermittent migraine was found in the patient, but the symptoms of occipital pain, nausea, and vomiting did not occur again. Lessons: For patients who have been diagnosed with SAH but have no definite cause, we should pay attention to the etiological screening of SAH, and the possibility of the spinal cord SAH should be vigilant. The pain in the chest and back and the signs of spinal cord may be an important breakthrough in patients with spinal cord SAH, and medical history and physical examination are particularly important.